Coronary Slow-Flow Phenomenon as an Underrecognized and Treatable Source of Chest Pain: Case Series and Literature Review - Chikezie Alvarez MD; Henry Siu MD, FACC, RPVI (SAGE Publishing, 2018)
Background . Coronary slow-flow phenomenon (CSFP) is characterized by delayed distal vessel opacification of contrast, in the absence of significant epicardial coronary stenosis. CSFP has been reported as a cause of chest pain and abnormal noninvasive ischemic tests and is often underrecognized. Material and Methods . Charts and angiographic records from our institution were reviewed to identify 15 consecutive patients who were diagnosed with CSFP from January 2016 to January 2017. Results . Of the 15 patients (4 females and 11 males) studied, the mean age was 59.1 years (range = 45-86 years); all had left ventricular ejection fraction >45% and without significant valvular stenosis/regurgitation. The indication for coronary angiography for all 15 patients was chest pain with abnormal noninvasive tests. Of the 11 patients who underwent previous coronary angiograms, all revealed prior evidence of CSFP. None of these patients were on calcium channel blockers (CCBs) or long-acting nitroglycerin agents before angiography. Intracoronary CCBs were effectively utilized to alleviate the angiographic finding (improvement in Thrombolysis in Myocardial Infarction frame count) in all 15 patients. Oral CCBs were started with subsequent improvement in all 15 patients (mean follow-up time = 13.6 months). Conclusion . Coronary slow-flow should be a diagnostic consideration in patients presenting with chest pain and abnormal noninvasive ischemic testing with nonobstructive epicardial vessels. CSFP remains underrecognized, and the specific standard of care for treatment has not been established. In each of the 15 cases, intracoronary nifedipine resolved the angiographic manifestation of coronary slow-flow. Furthermore, in follow-up, all patients improved symptomatically from their chest pain after oral CCBs were initiated.